Testing methods for antimicrobial activity of TiO2 photocatalyst - Markov Siniša L.; Vidaković Ana M. (Acta Periodica Technologica, 2014)
In recent years, a lot of commercial TiO2 photocatalyst products have been developed and extensively studied for prospective and safe antimicrobial application in daily life, medicine, laboratories, food and pharmaceutical industry, waste water treatments and in development of new self-cleaning and antimicrobial materials, surfaces and paints. This paper reviews the studies published worldwide on killing microorganisms, methods for testing the antimicrobial activity, light sources and intensities, as well as calculation methods usually used when evaluating the antimicrobial properties of the TiO2-based products. Additionally, some strengths and weaknesses of the available methods for testing the antimicrobial activity of TiO2 photocatalyst products have been pointed out.[Projekat Ministarstva nauke Republike Srbije, br. III45008]